Activation of the constitutive androstane receptor decreases HDL in wild-type and human apoA-I transgenic mice - David Masson (Journal of Lipid Research, 2008)
The nuclear hormone receptor constitutive androstane receptor (CAR, NR1I3) regulates detoxification of xenobiotics and endogenous molecules, and has been shown to be involved in the metabolism of hepatic bile acids and cholesterol. The goal of this study was to address potential effects of CAR on the metabolism of HDL particles, key components in the reverse transport of cholesterol to the liver. Wild-type (WT) mice, transgenic mice expressing human apolipoprotein A-I (HuAITg), and CAR-deficient (CAR−/−) mice were treated with the specific CAR agonist 1,4-bis[2-(3,5-dichloropyridyloxy)]benzene (TCPOBOP). CAR activation decreased HDL cholesterol and plasma apolipoprotein A-I (apoA-I) levels in both WT and HuAITg mice, but not CAR−/− mice. Both mouse apoA-I and human apoA-I were decreased by more than 40% after TCPOBOP treatment, and kinetic studies revealed that the production rate of HDL is reduced in TCPOBOP-treated WT mice. In transient transfections, TCPOBOP-activated CAR decreased the activity of the human apoA-I promoter. Although loss of CAR function did not alter HDL levels in normal chow-fed mice, HDL cholesterol, apoA-I concentration, and apoA-I mRNA levels were increased in CAR−/− mice relative to WT mice when both were fed a high-fat diet. We conclude that CAR activation in mice induces a pronounced decrease in circulating levels of plasma HDL, at least in part through downregulation of apoA-I gene expression.